2018
DOI: 10.1186/s12903-018-0516-4
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of early extraction of compromised first permanent molar: a systematic review

Abstract: BackgroundThe aim of this study was to systematically review the literature to determine the sequelae of early extraction of compromised first permanent molars (FPMs) with regard to the skeletal and dental development of 5- to 15-year-old children. Meta-analysis was conducted when applicable.MethodsOur research protocol included a search strategy, inclusion/exclusion criteria, and a data extraction plan. The search engines used were PubMed, Scopus, and Science Direct. Study selection was performed independentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 22 publications
2
44
0
7
Order By: Relevance
“…In this study, when a statistical model using regression analysis was undertaken to determine the factors affecting the success of spontaneous space closure, the presence of third molar was found to be statistically significant among all the variables. A recent systematic review included observational and retrospective studies mentioned that the consequences of FPM extraction include a decrease in post extraction space, via development and eruption of SPM and presence of third molar [12]. Eichenberger et al [26] also agreed that the presence of developing third molar could have a positive effect on spontaneous space closure compatible with our data in the mandibular arch.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In this study, when a statistical model using regression analysis was undertaken to determine the factors affecting the success of spontaneous space closure, the presence of third molar was found to be statistically significant among all the variables. A recent systematic review included observational and retrospective studies mentioned that the consequences of FPM extraction include a decrease in post extraction space, via development and eruption of SPM and presence of third molar [12]. Eichenberger et al [26] also agreed that the presence of developing third molar could have a positive effect on spontaneous space closure compatible with our data in the mandibular arch.…”
Section: Discussionsupporting
confidence: 87%
“…These teeth are commonly associated with short and long-term clinical dilemmas. In the literature, the incidence of developmental defects (hypomineralization)varies between 10% and 30% [12]. An report showed that primary indication for FPM extraction was extensive dental caries (70%) [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 The first permanent molar (FPM) erupts early in the oral cavity, thus becoming prematurely exposed to noxae, making it more prone to caries before 15 years of age. 2 In addition, it is the tooth most susceptible to developmental defects such as molarincisor hypomineralization (MIH). 3 The prevalence of MIH in children 6 to 12 years old in the Metropolitan Region of Santiago de Chile was 12.7%, mostly at 8 and 9 years of age.…”
Section: Introductionmentioning
confidence: 99%